Neurological outcome and inflammation after cardiac arrest: effects of protein C in rats - Teschendorf, Peter; Albertsmeier, Markus; Vogel, Peter; Padosch, Stephan A.; Spöhr, Fabian; Kirschfink, Michael; Schwaninger, Markus; Böttiger, Bernd W.; Popp, Erik (Resuscitation, 2008)
BACKGROUND: The response of the human body to cardiac arrest (CA) and cardiopulmonary resuscitation is characterised by excessive coagulation, inadequate endogenous anti-coagulation and fibrinolysis as well as an inflammatory syndrome that closely resembles the immunological profile observed in patients with sepsis. Recombinant human activated protein C (rhAPC) has been found to be protective in severe sepsis and in animal models of stroke and spinal cord injury. In the present study, we evaluated the effects of rhAPC on neurological outcome after CA in rats. METHODS: After 6 min of CA and subsequent cardiopulmonary resuscitation, male Wistar rats were randomized into 3 treatment groups: high dose rhAPC (2 mg/kg bolus and 0.1 mg/(kg h) for 6 h), low dose rhAPC (0.5 mg/kg and 0.025 mg/(kg h) for 6 h), and placebo (n=12 per treatment and reperfusion time). Neurological outcome was determined using a tape removal test and a composite neurological deficit score (NDS). As secondary measurements, we evaluated overall and neuronal survival, hippocampal caspase activity and inflammatory markers. RESULTS: No difference between groups was found with the NDS. The tape removal test showed only a transitory improvement in the low dose group at 3 d after CA (P=0.041). No significant differences were observed for secondary measurements. CONCLUSION: A clear and lasting effect of rhAPC on neurological outcome or inflammation after CA could not be shown in this study but the detailed analysis of the postresuscitation syndrome given here builds a firm basis for further research.
Gesehen am 18.06.2021